1985
DOI: 10.1097/00000658-198506000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Management of Gastric Ulcers

Abstract: In the past 10 years, 163 patients with documented gastric ulcers were treated at Vanderbilt University and Metropolitan Nashville General Hospitals. One hundred thirty-five were initially managed medically. Medical therapy was successful in 58 patients (43%) in this group. Twenty-eight (17%) patients required surgical treatment initially. An additional 77 patients (57%) became candidates for surgical management when their medical management failed. Of this group, 40 now have been surgically treated and 37 sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 21 publications
4
6
0
Order By: Relevance
“…According to the literature, the post-operative mortality of patients with perforated gastric ulcers [ 16 , 19 , 24 , 25 , 26 ] and perforated peptic ulcers [ 12 , 27 ] to be between ~10–20%, compared to <6% in the present study. A separate study found a 2.9% mortality in surgically treated patients with gastric ulcers, which was more in line with the findings of our study [ 28 ]. Interestingly, one randomized trial looking at perforated peptic ulcers found no differences in mortality between surgical and nonsurgical groups [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the literature, the post-operative mortality of patients with perforated gastric ulcers [ 16 , 19 , 24 , 25 , 26 ] and perforated peptic ulcers [ 12 , 27 ] to be between ~10–20%, compared to <6% in the present study. A separate study found a 2.9% mortality in surgically treated patients with gastric ulcers, which was more in line with the findings of our study [ 28 ]. Interestingly, one randomized trial looking at perforated peptic ulcers found no differences in mortality between surgical and nonsurgical groups [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…We cannot give an accurate figure for the overall incidence of HGU because we did not study the patients treated conservatively for this type of ulcer; however, HGU constituted approximately 4% of the total number of patients operated on for gastric ulceration. This corresponds with the figure of 4-5% quoted by others [1,2].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the ulcer is likely to recur after a local procedure to the ulcer, as occurred in one of our patients and in 40% of patients with more distal ulcers treated in this manner before the era of Hz-receptor blockers [29]. When used for bleeding ulcers, rebleeding is likely [1,2,29] as occurred with fatal outcome in one of our patients. A cancer may be overlooked, as discussed above.…”
Section: Oversewing Closure or Transfixion Onlymentioning
confidence: 85%
See 1 more Smart Citation
“…This philosophy is also shared by others [25,26] who have had a wide experience in ulcer surgery. The recent report by Adkins [27] in a review of the Vanderbilt series states the same opinion. For the type I Johnson ulcer, which is located along the incisura angularis delineating the parietal-antral junction, vagotomy is not necessarily included as a component of the resection unless the patient is an alcoholic or drug abuser.…”
Section: Choice Of Operation: Massively Bleeding Gumentioning
confidence: 80%